Youth Advocacy and Pedagogical Instructions as Efforts towards Climate Sustainability - Archibong, Emmanuel Iniobong; Afeku-Amenyo, Hilda; Orji, Patricia Chiamaka; Ademola, Temitope Oluwafemi; Justice, Ezechimere Ugochukwu; Joseph, Enobong Monday; Appea, Gifty Boahemaa (NIU Journal of Humanities, 2025)
Climate change undoubtedly is a pressing global issue which requires immediate attention and collective action. It is believed that youth can play a vital role in promoting sustainability and advocating for climate action. This is the motivation for the study as it x-rayed the impact of youth advocacy and pedagogical instructions on climate sustainability. The study examined the importance of education in empowering youth to contribute to sustainable development efforts. Adopting the theoretical framework of Albert Bandura's Social Learning Theory and Jack Mezirow's Transformative Learning Theory, the research emphasized the role of education in shaping youth's attitudes, behaviours, and actions towards climate sustainability. A comprehensive review of existing literature was conducted using a systematic review methodology which showed the need for curriculum revisions that centred on Indigenous knowledges, integrated climate justice, and the upholding of relationality to the land. The findings suggested that pedagogical instructions enhanced climate sustainability by equipping youth with appropriate knowledge, skills, and platforms to engage in climate action initiatives. Youth advocacy conclusively, is expected to promote policy changes, community engagement, and sustainable practices while mitigating the impact of climate change.  As an imperative therefore, the holistic and inclusive approach to climate education should foster a generation of climate-conscious and empowered youth who can contribute to a more sustainable future for all. Keywords: Youth Advocacy, Pedagogical Instructions, Climate Sustainability, Climate Education, Sustainable Development, Indigenous Knowledges, Climate Justice.